Evaluation of Multi-Bit Input Logic Blocks in RTL-Designed FPGA Architecture: A Framework for FPGA and ASIC Integration - Tomoaki Sato; Anyu Murakami; Sorawat Chivapreecha; Phichet Moungnoul (My University, 2025)
This paper explores the evaluation and optimization of multi-bit input logic blocks (LBs) within RTL-designed FPGA architectures. Traditional FPGA designs face limitations in power consumption, delay, and area due to the constraints of reconfigurable circuits. The proposed architecture leverages RTL-level design capabilities to address these challenges and enables the co-design of FPGAs and ASICs. The authors evaluate the performance of 8-bit, 16-bit, and 32-bit input LBs in terms of delay, area, and synthesis feasibility. The results demonstrate that 8-bit input LBs achieve a delay of 0.68 ns with an area of 2202.48 μm2, outperforming multi-stage smaller LBs. Although 16-bit input LBs show potential for delay reduction, their synthesis demands significant time and results in a large area footprint, rendering them impractical. Synthesis of 32-bit input LBs was not feasible due to current tool limitations. These findings highlight the effectiveness of 8-bit input LBs for pattern matching tasks and emphasize the importance of application-specific optimization. The fixed routing feature of RTL-designed FPGAs facilitates the development of efficient, customizable designs tailored to specific workloads. This work contributes to the advancement of FPGA architectures, offering insights for future research on larger input LBs and their integration into high-performance applications.
Keywords: Embedded Systems Design Techniques; Low-power high-performance VLSI design; Electromagnetic Compatibility and Noise Suppression